1982
DOI: 10.1002/ijc.2910300405
|View full text |Cite
|
Sign up to set email alerts
|

Papillary carcinomas of the thyroid have pore‐deficient nuclei

Abstract: A significant reduction in nuclear pore density observed in papillary carcinomas compared to normal thyroid, adenomas and follicular carcinomas probably disturbs the nucleo-cytoplasmic transfer of ribonucleoproteins. This may contribute to the slow growth and indolent biological behavior of these tumors where even the presence of regional lymph node metastases does not worsen the prognosis. The signs of nuclear hyperactivity may result from an attempt to compensate for the nuclear membrane defect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…(3,4) state that it is an artifact, but that it has some basis in fact-perhaps peculiar physical and/or chemical properties of the chromatin. Ultrastructural studies of these nuclei have shown finely dispersed chromatin, a highly folded nuclear membrane, and a paucity of nuclear pores (16,17).…”
Section: Introduction the Diagnosis Of Follicular Carcinoma Of The Thmentioning
confidence: 99%
“…(3,4) state that it is an artifact, but that it has some basis in fact-perhaps peculiar physical and/or chemical properties of the chromatin. Ultrastructural studies of these nuclei have shown finely dispersed chromatin, a highly folded nuclear membrane, and a paucity of nuclear pores (16,17).…”
Section: Introduction the Diagnosis Of Follicular Carcinoma Of The Thmentioning
confidence: 99%
“…1) and is becoming more readily applied in the clinical setting 154 . There are indications in the literature that higher NPC numbers are associated with more aggressive tumours 155158 . The quantitative assessment of NPCs is now possible with high-resolution light microscopy (for example, see REF.…”
Section: Applying Knowledge Of the Nuclear Envelopementioning
confidence: 99%
“…[37]). In the literature, increases in the number of NPCs were related with more aggressive tumors [38,39,40,41].…”
Section: Introductionmentioning
confidence: 99%